1995
DOI: 10.1021/tx00044a017
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Glutathione Adducts of 4-(Dimethylamino)phenol. Formation of a Highly Reactive Cyclization Product

Abstract: During ferrihemoglobin formation, 4-(dimethylamino)phenol (DMAP), a potent cyanide antidote, forms a quinoid compound that is prone to sequential oxidation/addition reactions. In human red cells and hemoglobin solutions fortified with glutathione, a transient adduct has been isolated and identified as 4-(dimethylamino)-2-(glutathion-S-yl)phenol (2-GS-DMAP). This compound still formed ferrihemoglobin but differed from parent DMAP in that the reaction rate was roughly proportional to the oxygen concentration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…GSH conjugate 20 was shown to be a Cys-Gly conjugate whose formation can be rationalized via the generation of an ortho -quinone intermediate 18 from GSH adduct 17 , loss of the γ-glutamic acid residue from one of the adducted GSH molecules to yield 19 , and intramolecular condensation of the cysteinyl primary amine group with an adjacent carbonyl in 19 to form the ortho -benzoquinoneimine/GSH conjugate 20 . Structurally similar Cys-Gly adducts have also been observed with para -aminophenol and catechol derivatives. …”
Section: Reaction Of Aledhydes With Cysteine or Gshmentioning
confidence: 75%
See 1 more Smart Citation
“…GSH conjugate 20 was shown to be a Cys-Gly conjugate whose formation can be rationalized via the generation of an ortho -quinone intermediate 18 from GSH adduct 17 , loss of the γ-glutamic acid residue from one of the adducted GSH molecules to yield 19 , and intramolecular condensation of the cysteinyl primary amine group with an adjacent carbonyl in 19 to form the ortho -benzoquinoneimine/GSH conjugate 20 . Structurally similar Cys-Gly adducts have also been observed with para -aminophenol and catechol derivatives. …”
Section: Reaction Of Aledhydes With Cysteine or Gshmentioning
confidence: 75%
“…The major metabolic pathway of 24 in the central nervous system involves oxidative deamination by monoamine oxidase (MAO) to afford 5-hydroxyindole-3-acetaldehyde (25), which is converted to 5hydroxyindole-3-acetic acid (26) by aldehyde dehydrogenase (ALDH). A minor pathway involves the reduction of 25 to the primary alcohol 5-hydroxytryptophol (27) by aldehyde reductase. Singh and Dryhurst 39 demonstrated that incubation of 24 with NADPH-and L-cysteine (or GSH)-supplemented pig or bovine brain microsomes or with synaptosomes resulted in the formation of the (2R,4R)-and (2S,4R)-epimers of 2-[(5hydroxy-1H-indol-3-yl)methyl]thiazolidine (compounds 28 and 29, respectively) or α-amino-4-[[(carboxymethyl)amino]carbonyl]-2-[(5-hydroxy-1H-indol-3-yl)methyl-δ-oxo-3-thiazolidinepentanoic acid (compounds 30 and 31, respectively) from a reaction of cysteine or GSH with the aldehyde 25.…”
Section: Literature Examples Pertaining To Cyclizedmentioning
confidence: 99%
“…Reactive metabolite trapping screens with liver microsomes (usually human) fortified with nucleophiles such as GSH, cysteine, potassium cyanide, and methoxylamine are routinely employed to trap reactive electrophilic species at sufficient concentration to form stable, recognizable products/adducts which can be identified by their expected MS changes. However, unexpected or structurally unusual products from nonstandard biotransformations such as structural rearrangements could escape detection during the MSMS investigations due to changes in molecular structure, molecular weight, and the lack of expected fragmentation patterns. Of particular concern are cyclized GSH adducts which can produce a false negative result in conventional LC-MSMS GSH trapping screens, as GSH adducts are generally identified by their expected target mass, a neutral loss of 129 Da in positive ion mode, or/and a m / z of 273 in a precursor ion scan in negative ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…However, unexpected or structurally unusual products from nonstandard biotransformations such as structural rearrangements could escape detection during the MSMS investigations due to changes in molecular structure, molecular weight, and the lack of expected fragmentation patterns. Of particular concern are cyclized GSH adducts which can produce a false negative result in conventional LC-MSMS GSH trapping screens, as GSH adducts are generally identified by their expected target mass, a neutral loss of 129 Da in positive ion mode, or/and a m / z of 273 in a precursor ion scan in negative ion mode.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we decided to systematically investigate oxidation versus arylation reactions of the compounds and to correlate the reaction pathways with physicochemical properties of the isolated thioethers. The following articles (56,57) will deal with the reactivity of the DMAP thioethers and with the role reactive oxygen species are playing when DMAP thioethers react with oxyhemoglobin. hemoglobin ( I I ) , are the most important ones.…”
Section: Introductionmentioning
confidence: 99%